2020
DOI: 10.1136/bmjopen-2020-038987
|View full text |Cite
|
Sign up to set email alerts
|

Social burden of people with the migraine diagnosis in Japan: evidence from a population-based cross-sectional survey

Abstract: ObjectivesTo quantify the social burden among Japanese migraine patients in the context of currently available migraine treatments, by comparison with non-migraine controls, and comparison of migraine patients currently taking prescription medication versus not taking prescription medication.DesignCross-sectional analysis.SettingData from the population-based online self-administered Japan National Health and Wellness Survey (NHWS) 2017.ParticipantsRespondents to the NHWS (n=30 001) were ≥18 years. Migraine pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
(47 reference statements)
4
7
0
Order By: Relevance
“…Igarashi et al . 25 reported presenteeism of 32.73% and absenteeism of 6.95% in patients diagnosed with migraine, and the same decline in work performance in axillary hyperhidrosis patients as observed in our survey. Sruamsiri et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Igarashi et al . 25 reported presenteeism of 32.73% and absenteeism of 6.95% in patients diagnosed with migraine, and the same decline in work performance in axillary hyperhidrosis patients as observed in our survey. Sruamsiri et al .…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the annual societal loss associated with productivity loss was ¥2.5 trillion (approximately ¥208.3 billion/month). Igarashi et al25 reported presenteeism of 32.73% and absenteeism of 6.95% in patients diagnosed with migraine, and the same decline in work performance in axillary hyperhidrosis patients as observed in our survey. Sruamsiri et al26 conducted a Web-based survey on 500 pa-…”
supporting
confidence: 89%
“…Their result indicates that 16% of workforce presenteeism may be due to migraine with a cost of US $240 billion dollars per year. Furthermore, according to the Japan National Health and Wellness Survey of pooled commercial data, migraine patients have been reported to experience significantly higher presenteeism than controls in Japan [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Impairment was greater in people with migraine in the OVERCOME (Japan) study than has been reported for people without migraine. In a direct comparison of Japanese people with and without migraine, using data from the Japan NHWS, those without migraine had total work impairment scores of only 20% and total activity impairment scores of 22% [ 12 ]. WPAI-M absenteeism scores in OVERCOME (Japan) ranged from 3.8% in the LFEM group to 6.2% in the CM group.…”
Section: Discussionmentioning
confidence: 99%
“…These surveys revealed a high burden of disease among Japanese people with migraine, including substantial proportions of people requiring bed rest during migraine attacks, experiencing moderate-to-severe impacts on social activity, requiring time off work, and experiencing a general perception of poor health [ 5 , 6 ]. More recently, an analysis of data from the Japan National Health and Wellness Survey (NHWS) in 2017 revealed that people with a migraine diagnosis had poorer health-related quality of life (HRQoL) and more impairment to work productivity than matched controls without migraine [ 12 , 13 ]. A recent workplace-based survey conducted in a Japanese information technology company revealed a high prevalence and burden of migraine among employees and substantial associated economic costs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%